Reasons behind Spousal Aggression in A Thousand Splendid Suns by Khaled Hosseini - Neupane, Dasarath; Khanal, Ramnath (Journal of Advanced Academic Research, 2018)
The theme of the study was in-depth study of reasons behind spousal (in this study husband-to-wife) aggression from the novel A Thousand Splendid Suns by Khaled Hosseini. In this study, reasons behind Rasheed's aggression were taken as the central attention, and illustrated different theories related to aggression. The study applied psychological approach to assess reasons behind husband-to-wife aggression in the novel. The researcher applied the ethological theory, social learning theory and drive theory to assess reasons behind the kinds of aggression that Rasheed commits on his wives. The findings of the study indicate that Rasheed is a man with a big body and possesses a gun, which provides more chances for him to commit aggression over his wives. The drive theory addressed in this matter provides an understanding that aggression is produced by frustration. In other words, frustration-aggression hypothesis is the reason proposed by drive theory. Herein Rasheed’s aggression analysis, this theory helps to yield two findings that Rasheed’s sources of frustration are first, his encounter with his old-painful experience of losing a son, and the second is his sad condition over losing all his jobs and lacking foods to eat. The last but not least is the social learning theory, which proposes a help to see the surrounding of aggression as also the consideration for its initiation. The conclusion of this view is male domination-especially in the marriage system – in Afghanistan provide more spaces for man to aggress against woman as a wife. The story implies that it has been common in Afghanistan to find polygamous husband living under one roof. The second conclusion is that Taliban’s ruling is a possible role model for the male Afghans to commit harassment towards woman, as Taliban tends to force women into corner by enacting many banning and restriction upon them. Without termination on that, this group sets a deadly punishment to a-find-guilty woman by stoning them to death on a football field surrounded by large of people (men) who favour to Taliban.